2021
DOI: 10.3390/cells10061426
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Ganglion Cell Transplantation: Approaches for Overcoming Challenges to Functional Integration

Abstract: As part of the central nervous system, mammalian retinal ganglion cells (RGCs) lack significant regenerative capacity. Glaucoma causes progressive and irreversible vision loss by damaging RGCs and their axons, which compose the optic nerve. To functionally restore vision, lost RGCs must be replaced. Despite tremendous advancements in experimental models of optic neuropathy that have elucidated pathways to induce endogenous RGC neuroprotection and axon regeneration, obstacles to achieving functional visual reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 194 publications
(232 reference statements)
0
48
0
Order By: Relevance
“…The reader is referred to complimentary sources for derivation of retinal explant cultures from those species ( Bull et al., 2011 ; Wang et al., 2011 ; Januschowski et al., 2012 ; Peynshaert et al., 2017 ). We have documented that proteolytic digestion of the internal limiting membrane (ILM) with the enzyme Pronase facilitates the structural engraftment of donor RGCs into the host retina ( Zhang et al., 2021a , 2021b ), and so steps to achieve ILM disruption are included here. For complete details on the generation and use of this protocol, please refer to ( Zhang et al., 2021a , 2021b ).…”
Section: Before You Beginmentioning
confidence: 99%
See 2 more Smart Citations
“…The reader is referred to complimentary sources for derivation of retinal explant cultures from those species ( Bull et al., 2011 ; Wang et al., 2011 ; Januschowski et al., 2012 ; Peynshaert et al., 2017 ). We have documented that proteolytic digestion of the internal limiting membrane (ILM) with the enzyme Pronase facilitates the structural engraftment of donor RGCs into the host retina ( Zhang et al., 2021a , 2021b ), and so steps to achieve ILM disruption are included here. For complete details on the generation and use of this protocol, please refer to ( Zhang et al., 2021a , 2021b ).…”
Section: Before You Beginmentioning
confidence: 99%
“…We have documented that proteolytic digestion of the internal limiting membrane (ILM) with the enzyme Pronase facilitates the structural engraftment of donor RGCs into the host retina ( Zhang et al., 2021a , 2021b ), and so steps to achieve ILM disruption are included here. For complete details on the generation and use of this protocol, please refer to ( Zhang et al., 2021a , 2021b ).…”
Section: Before You Beginmentioning
confidence: 99%
See 1 more Smart Citation
“…It is currently difficult to fully distinguish bona fide synaptic connections from existing ones—however rare they may be—in the absence of direct and effective methods for studying synaptic contacts of donor cells. 34 , 204 A recent study by Cowan et al suggests that PRP are capable of forming functional synapses within retinal organoids as evidenced by calcium imaging. 134 However, no study to date has definitively shown that hPSC-PRPs can form new functional synapses after being isolated from retinal organoids.…”
Section: Current Status and Remaining Questions For Retinal Cell Therapiesmentioning
confidence: 99%
“…This aim might be achieved by the transplantation of RGCs derived from embryonic stem cells or induced pluripotent stem cells. While the generation of RGCs from pluripotent stem cells has made considerable progress, RGC replacement by cell transplantation is faced with a number of problems that need to be solved before restoration of meaningful vision might be achieved, such as functional integration of specific RGC subtypes into the dystrophic retinas or long-distance growth of axons and the formation of functional synapses in visual target regions of the brain [ 33 , 34 , 35 , 36 , 37 ]. Most current therapeutic approaches therefore aim to delay or prevent the degeneration of those RGCs that are still viable at initial stages of the disease.…”
Section: Introductionmentioning
confidence: 99%